APPLICATION OF NATURAL LANGUAGE PROCESSING IN INFORMATION SECURITY - Rakhmanov K. S. (Web of Journals Publishing, 2025)
Natural Language Processing (NLP) has emerged as a powerful tool in the field of information security, enabling automated detection and analysis of textual threats such as phishing emails, malicious URLs, social engineering attempts, and insider threats. This paper explores the key applications of NLP in cybersecurity, presents commonly used techniques and models, and discusses their effectiveness and limitations.
Keywords: NLP, Information Security, Phishing Detection, Threat Analysis, Cyber security, Text Mining, AI Security